Online movie rental system / Lim Kwang Yoong - Lim , Kwang Yoong (2003)
The online movie rental system is actually a web site that consist of a number of web pages; the idea of developing this online system is come out with the observation to the current movie rental system that normally a close system (not a web enabled system), especially the reservation method that is usually carried out manually at video center. Nowadays, so many online movie rental systems can be found on Internet, as their usages are basically for publishing products (movies as well) by service provider, advertising services and products, and communicates with either website visitors or members. The architecture of online system of this project is two-tier client/server architecture. First tier of the architecture is a user of this online system, visitor, member or administrator. Second tier will be the database, which store key data essential for the system. The project of developing this online system is separated into a few phases (chapters). Each phase discusses different but related issues and activities that is essential for the whole project. The first chapter of this project documentation discusses the project introduction and definition. The second chapter discusses about literature review of the existing systems and the potential development tools for this project. The following chapter, chapter 3 discusses the methodology of software engineering. Chapter four is about the system analysis to capture functional and non-functional requirements of the system, and also determine the development requirements, including hardware and software consideration for developing this project. Chapter 5 discusses the system design and database design describing in tables, figures and UML diagrams.